Artificial weathering aging of PPT coatings made from recycled PET to protect concrete: Nanomechanical properties evaluation - Adrián Bórquez-Mendivil; Jorge Luis Almaral-Sánchez; Jesus Eduardo Leal-Perez; César Modesto-Acosta; Joaquin Flores-Valenzuela; Orlando Auciello; Blanca Alicia García-Grajeda; José Miguel Mendivil-Escalante; Sergio G. Flores-Gallardo; Roberto P. Talamantes-Soto; Abel Hurtado-Macías (Journal of Materials Research and Technology)
The objective of this work was to artificial weathering age polypropylene terephthalate (PPT) coatings obtained from polyethylene terephthalate (PET) recycled for the evaluation of their nanomechanical properties, which are proposed for the protection of hydraulic concrete. PPT was polymerized by transesterification from recycled PET containers using glycolysis. Besides, PPT used to produce coatings on glass substrates via the dip coating method. The morphology and microstructure were analyzed by scanning electron microscopy (SEM) and atomic force microscopy (AFM); with these techniques, it was possible to identify the deterioration of the coating (porosity and origin of cracks) and the increase in roughness (6 ± 1 nm to 746 ± 5 nm), respectively. Likewise, the nanomechanical properties, such as hardness by indentation (Hi), hardness by scratching (Hs), and elastic modulus (E), of the PPT coatings were evaluated by the depth sensing indentation method depending on their aging treatment. The analysis of the molecular degradation of the PPT coatings was performed by Fourier transform infrared spectroscopy (FT-IR), which revealed that the rupture of C–H bonds caused the nanomechanical properties of the coatings to decrease; Hi = 200 ± 5 MPa to Hi = 32 ± 18 MPa, Hs = 125 ± 12 MPa to Hs = 12 ± 5 MPa and E = 5.1 ± 1.01 GPa to E = 1.05 ± 0.23 GPa.